A study of the interaction between vine vigour, crop level and harvest dates and their effects on grape and wine characteristics - Quixley, Pieter C (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MscAgric (Viticulture and Oenology))--University of Stellenbosch, 2007.